Performance of Maize Cultivars for Fodder Production under Rainfed Conditions of Pothohar Tract (Biological Sciences - PJSIR, 2008)
. For finding the forage yield potential of eight maize cultivars, the cultivars were sown in the month of July during both consecutive years 2001 and 2002 and harvested in the month of September in both the years. The cultivars differed significantly from one another with regard to plant height, number of leaves per tiller, number of plants per row, leaf area per plant, green fodder and dry matter yield. The cultivar ‘Akbar’ produced taller plants, with the largest leaf area and more number of leaves per tiller and consequently yielded highest amount of green as well as dry matter among all the varieties under the rainfed climatic conditions of Pothohar tract of Pakistan.